Kinematics Of Kshm of Internal Combustion Engines - Kholbekov Toshturdi Kudratovich; Amonov Chori Eshquvvatovich; Omanov Elmurod Nosir (Genius Journals, 2023)
Kinematics of the crank mechanism in internal combustion engines single-stage engine. The calculation of the crank mechanism is given.
Keywords: Kinematics; crankshaft; engines; connecting rod